2017
DOI: 10.1016/j.heliyon.2017.e00382
|View full text |Cite
|
Sign up to set email alerts
|

Cooking methods affect phytochemical composition and anti-obesity potential of soybean ( Glycine max ) seeds in Wistar rats

Abstract: This work aimed at investigating the effects of three domestic cooking methods (roasting, sprouting and boiling) on phytochemical contents (phenolic content, flavonoid, fibre), and anti-obesity (weight loss, hypoglycemic effect, serum lipids) potential of soybean seeds in obese male rats. Ten different forms were implemented, combining hulled/unhulled and raw/cooked soybean seeds using a basal and a hypercaloric diet as controls. Unhulled Roasted Soybean (URS) exhibited the highest phenolic content and a great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 29 publications
(30 reference statements)
2
10
0
Order By: Relevance
“…Plants rich in secondary metabolites including phenolics and flavonoids demonstrate powerful antioxidant properties, both in vitro and in vivo, which is attributed to their redox properties and chemical structures [35,36,37]. The results of the previous studies are also similar to ours [28,30,31,32,33,38].…”
Section: Resultssupporting
confidence: 80%
“…Plants rich in secondary metabolites including phenolics and flavonoids demonstrate powerful antioxidant properties, both in vitro and in vivo, which is attributed to their redox properties and chemical structures [35,36,37]. The results of the previous studies are also similar to ours [28,30,31,32,33,38].…”
Section: Resultssupporting
confidence: 80%
“…In addition, anti-inflammatory effects, such as inhibition of prostaglandin 2 (PGE2), and IL-1β were confirmed in RAW264.7 cells for black soybean extract [ 7 ], and when black soybean extract was administered to a diet-induced obesity (DIO) mouse model, decreases in TNF-α and IL-6 were observed, which are anti-inflammatory markers [ 8 ]. In previous studies related to obesity, isoflavone components in soybeans lowered blood lipid levels, thereby decreasing the risk of obesity and cardiovascular diseases [ 9 ], and when boiled and peeled soybeans were administered to Wistar rats among soybean recipes, lower cholesterol and weight were observed [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many strategies have been put in place to manage this disease; these include the use of chemicals drugs and hypocaloric diets. Hypocaloric diets are slow in producing desired results while drugs, besides their side effects, are expensive (Kuate, Kengne, Biapa, Azantsa, & Muda, ; Woumbo, Kuate, & Womeni, ). This explains the renewed interest on research in functional foods for the diabetes management.…”
Section: Introductionmentioning
confidence: 99%
“…This explains the renewed interest on research in functional foods for the diabetes management. In addition, epidemiological studies and clinical trials have shown that dietary intake of vegetables is correlated with a reduced risk of development of chronic diseases such as cancer, type 2 diabetes, and others (Woumbo et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation